Fortified farm yard manure to bio-stimulate nutrient availability and production of Indian mustard - Mukesh Kumar Meena; Ram Swaroop Jat; Mohan Lal Dotaniya; Murli Dhar Meena; Vasudev Meena; Vijay Singh Meena; Ibandalin Mawlong; Ram Lal Choudhary; Harvir Singh; Hari Singh Meena; Vijay Veer Singh (PLoS ONE, 2026)
Fortified farm yard manure (FYM) enriched with secondary and micronutrients were prepared, and its effects on mitigating the decline in soil health, nutrient availability, and yield levels in Indian mustard under calcareous soil were assessed. FYM at 10 tonnes ha -1 and FYM (500 kg ha -1 ) fortified with 20 kg S + 5 kg Zn + 2 kg B + 10 kg Fe significantly improved seed yield and growth parameters of mustard. However, the highest benefit-cost ratio (4.22) with a seed yield of 28.72 q ha -1 was obtained under the application of half dose of the recommended levels of secondary and micronutrient, i.e., 2.5 kg Zn + 1 kg B + 5 kg Fe + 10 g S enriched FYM 500 kg ha -1 . This indicates that application of a balanced amount of micro and secondary nutrients through 500 kg FYM improved mustard yield and economic return to the farmers. Nutrient enrichment with micro and secondary nutrients at the rate of 5.0 kg Zn + 2 kg B + 10 kg Fe + 20 kg S enriched FYM @ 500 kg ha -1 significantly increased the soil microbial biomass carbon (56.46% SMB-C), soil organic carbon (SOC) (17.13%), and microbial biomass nitrogen (71.14% MBN) over the control. Moreover, nutrient fortification significantly improved the dehydrogenase activity (56.27%), alkaline phosphatase (101.44%) and aryl sulphatase (73.7%) in soil over control. The availability of S, Zn, Fe, and boron rose by 17.74%, 127.68%, 43.41%, and 52.76%, respectively, compared to the control. The utilization of FYM enriched with secondary and micronutrients at the rate of FYM 500 kg ha -1 is an effective technological strategy to improve soil health and production of Indian mustard in semi-arid environments.